2021
DOI: 10.7324/jabb.2021.9109
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological changes induced by ectoparasites on gills and skin of Oreochromis niloticus (Burchell 1822) in fish ponds

Abstract: Histopathological changes induced by ectoparasites on gills and skin of Oreochromis niloticus (Burchell 1822

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Conversely, in a study by Suliman et al (2021) where there was a substantial deterioration of fish pond water of Oreochromis niloticus, sampled water showed low oxygen, high ammonia, and nitrite with the examined fish presenting with severe alterations, blood hemorrhage, the fusion of secondary lamella, erosion and mucus secretions of the gills and the disease severity resulting in the death of some individuals. The histopathology of the fish gills indicated ectoparasites, one of which was Trichodina.…”
Section: Microscopic Examinationmentioning
confidence: 90%
“…Conversely, in a study by Suliman et al (2021) where there was a substantial deterioration of fish pond water of Oreochromis niloticus, sampled water showed low oxygen, high ammonia, and nitrite with the examined fish presenting with severe alterations, blood hemorrhage, the fusion of secondary lamella, erosion and mucus secretions of the gills and the disease severity resulting in the death of some individuals. The histopathology of the fish gills indicated ectoparasites, one of which was Trichodina.…”
Section: Microscopic Examinationmentioning
confidence: 90%
“…The presence of parasites in fish gills reduces the gill surface area, causes disturbances of hydromineral balance, increases ATP-ase expression and induces apoptosis in mitochondria-rich cells ( Oğuz & Oğuz, 2020 ). This mechanism causes reduced oxygen entering the fish, the color of the gills becomes pale, uncertain movement, fade color, stress, and even mortality ( Suliman et al, 2021 ). Besides gills, skin is a favorite place for parasites to attach.…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that histopathological analysis for parasites in fish is a valuable tool for fish health monitoring. Similarly, Suliman et al (2021) found that histopathological changes induced by ectoparasites on fish gills and skin could be used to determine the severity of ectoparasite infection, which can help improve fish farm management and produce healthier fish for human consumption.…”
mentioning
confidence: 99%